Commodity Based Associations - ’Offering Potential for Farmers’ Prosperity - Gopala, Y.M.; Narayana Gowda, K.; Nataraju, M.S; Lakshminarayan, M.T. (Journal of Agricultural Extension Management, 2019)
The paper analyses the impact of Commodity Based Associations (CBAs), grassroot level autonomous registered bodies established around a single enterprise, on income enhancement, employment generation and social status of the member producers. The results revealed that, the mean annual net income of the members before their participation in CBAs was Rs. 55,171 which rose to Rs. 70,378 after their membership. The mean annual employment generation was 390.28 mandays and 437.20 mandays during pre and post formation of CBAs, respectively. The mean social status score of CBA members before their participation was 7.80 while it was 15.08 after their membership. Indian farmers are facing many problems such as decreased profit margin, lack of employment, poor market linkages, etc. on account of issues like continuous fragmentation of landholdings, emergence of nuclear family system, a steep increase in the cost of production and others. This has led to large scale migration particularly of farm youth to urban areas. Findings suggest that producers associations have the potential to help farmers overcome many challenges and continue in farming through enhanced income, better living and ensured food security.